Mothers' Talk about Perceptions, Wants, Feelings, and Thoughts during Play: General or Specific Relations to Infants' Internal State Vocabularies and Gender?. Issue 2 (2nd April 2020) - Olson, Janet; Masur, Elise
ABSTRACT: The current study examined how mothers' production of four types of internal state words at multiple ages across the second year in a free play context was related to their infants' acquisition of those words. Twenty-nine mother-infant dyads were videotaped for 18 minutes during free play when infants were 13 and 17 months old. Mothers' total and number of different internal state words—subcategorized as disposition (like, happy), perception (see, hear) volition (want, need), and cognition (think, know) —were obtained. Infants' total and internal state subcategory vocabularies were measured with the MacArthur-Bates Communicative Development Inventory at 13, 17, and 21 months. Maternal internal state speech at 13 months was related to infants' overall concurrent receptive lexicons, while mothers' volition words at 13 months predicted infants' receptive total and internal state vocabularies at 17 months. Mothers' different perception words at 17 months were linked to infants' concurrent perception lexicons. Furthermore, mothers' different disposition words at 17 months predicted children's expressive disposition vocabularies at 21 months. These findings illuminate the value of examining subcategories of mothers' internal state speech in free play and reveal a shift over time from general to specific relations between mothers' and infants' internal state language.